PENGARUH PENGGUNAAN MIND MAPPING TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS V MIN 3 PONTIANAK - Safitri, Diah Eka; Kresnadi, Hery; Asmayani, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was to analyze the effect of the use of Mind Mapping on Thematic Learning Outcomes of Grade V Madrasah Ibtidaiyah 3 Pontianak students and analyze how high the effect of Mind Mapping on Thematic Learning Outcomes of Grade V Madrasah Ibtidaiyah Negeri 3 Pontianak students. The research method used is an experimental method in quasi-experimental design forms, with nonequivalent control group experimental design. The sample selection uses a purposive sampling technique. Based on statistical calculations the average results of the final test of the experimental class 70.67 and the average final test results of the control class 65.24 obtained of 2.922 and (α = 5% and dk 41 + 39 - 2 = 78) equal to 1,677, because t_ (count) (2,922)> (1,677), then Ha is accepted. From the calculation of the effect size (ES), ES 0.46 (medium criteria) was obtained. This means that the use of Mind Mapping has a moderate effect on the thematic learning outcomes of Grade V Madrasah Ibtidaiyah Negeri 3 Pontianak students. Keywords: Effect, Learning Outcomes, Mind Mapping, Thematic Learning.